The Possibility of Local Soils Use for Levees Construction as Part of Flood Protection - Korniichuk, Volodymyr; Shumlyanskyj, Andrii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The levee is an important part of the complex of flood protection measures, which is direct a barrier against high water levels. At the same time, it is the most voluminous and time-consuming structure, the construction of which requires a significant amount of material and transport costs. For their construction, soil from local quarries can be used, which will significantly reduce the costs of their construction and speed it up. But before the possibility of their use, it is necessary to check their suffusion characteristics to ensure their seepage stability.